(untitled) (Research, Society and Development, 2020)
The National School Feeding Program (NSFP) is the oldest Brazilian school feeding policy. In 2009, with the enactment of Law No. 11,947, the Program, in addition to covering the entire public basic education network, creates a new market for family farmers, by ensuring that at least 30% of the transfers from the National Development Fund for Education (NDFE) should be used to purchase food from family farming. Despite its undeniable importance in the area of food and nutrition security, as well as in local development, the budgetary execution of the NSFP by the Federal Institutes of Education, Science and Technology has been difficult to implement. Since the implementation and operationalization involves social interactions between several actors, as well as the discretion and other institutional elements, the aim of the present study was to show how different implementing actors, and their social interactions mediated by institutional elements, can stimulate particular dynamics of implementation of the Program. Therefore, the study was carried out in the Instituto Federal de Educação, Ciência e Tecnologia de Minas (IFMG) Campus São João Evangelista. A qualitative and quantitative approach, bibliographic, documentary, interviews and focus group study were carried out. The results showed that relational and institutional elements adopted locally, could influence the implementation and results of public policies. Another relevant factor concerns the “how” street-level bureaucrats exercise their discretions, the way they establish their links, the way they interpret the Program, the way they establish agreements, how they determine rules as well as the specifics of the local dynamics, and yet, the proximity that these actors must establish with family farmers.